2007
DOI: 10.1016/j.ydbio.2007.08.048
|View full text |Cite
|
Sign up to set email alerts
|

D-JNK signaling in visceral muscle cells controls the laterality of the Drosophila gut

Abstract: Although bilateral animals appear to have left-right (LR) symmetry from the outside, their internal organs often show directional and stereotypical LR asymmetry. The mechanisms by which the LR axis is established in vertebrates have been extensively studied. However, how each organ develops its LR asymmetric morphology with respect to the LR axis is still unclear. Here, we showed that Drosophila Jun N-terminal kinase (D-JNK) signaling is involved in the LR asymmetric looping of the anterior-midgut (AMG) in Dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
47
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 44 publications
7
47
0
Order By: Relevance
“…Our results showed that the mesodermal tissue also plays an essential role in the LR asymmetric development of the anterior midgut in D. melanogaster (Taniguchi et al, 2007b). Therefore, mechanisms of the mesoderm-derived LR asymmetric morphogenesis of the gut may be conserved between vertebrates and invertebrates.…”
Section: Genes Affecting Lr Asymmetry Development In D Melanogastermentioning
confidence: 61%
See 4 more Smart Citations
“…Our results showed that the mesodermal tissue also plays an essential role in the LR asymmetric development of the anterior midgut in D. melanogaster (Taniguchi et al, 2007b). Therefore, mechanisms of the mesoderm-derived LR asymmetric morphogenesis of the gut may be conserved between vertebrates and invertebrates.…”
Section: Genes Affecting Lr Asymmetry Development In D Melanogastermentioning
confidence: 61%
“…This result suggests that Rac1 acts upstream of D-JNK signaling in the LR asymmetric rearrangement of the visceral muscle cells (Taniguchi et al, 2007b).…”
Section: Genes Affecting Lr Asymmetry Development In D Melanogastermentioning
confidence: 82%
See 3 more Smart Citations